(untitled) (Docentes 2.0 Journal, 2026)
Reading comprehension is an essential competence in education, especially at the secondary level. This research aimed to review recent scientific literature on reading comprehension among secondary students. The goals were to identify theoretical approaches, pedagogical strategies, and key findings that support its improvement. The study used a positivist paradigm. It followed a systematic method, a mixed-methods approach, a narrative-thematic design, and a documentary-analytical type within a cross-sectional scope. Researchers reviewed 20 scientific articles from 2020 to 2025. They searched Scopus, WoS, Dialnet, SciELO, and Google Scholar, using the PRISMA protocol guidelines. The findings show that current research highlights strategies focused on higher-order reading skills, like extracting explicit information, making inferences, and forming critical responses. The research also identified factors that influence reading comprehension. These include types of digital technologies, features of post-pandemic instruction, and active learning methods. The evidence reviewed suggests that reading comprehension in secondary education is now studied critically. Teachers, digital contexts, and active learning methods all play important roles in strengthening students’ reading skills.